Sue for Disputes Resolution of Land Conflict in South Sumatera - Kholek, Abdul; Alfitri, Alfitri (Komunitas, 2017)
This paper aims to examine the roots, dynamics, and resolutions of land conflict between Rengas farmers and Limbang Jaya farmers with PTPN VII Cinta Manis in Ogan Ilir, South Sumatra. Authors use qualitative method through deepening data from depth interviews, observation and Focus Group Discussion (FGD). The results showed that the roots of the conflict are different foundation claims, lack of transparency in the mechanism of compensation, land grabbing by companies. The key findings of the conflict dynamics study was that conflict between farmers of Rengas with PTPN VII Cinta Manis led to reclaiming action by farmers which was regarded as a victory for the resistance of farmers in conflict. This reclaiming action attracted more regions into the conflict contestation, including farmers of Limbang Jaya. Rengas conflict and Limbang Jaya conflict was different: Rengas conflict had history of resistance since the beginning, while the conflict of Limbang Jaya was an escalation of the Rengas conflict. Conflict resolution was taken through advocating by civil society element and mediation by stakeholders. Both resolutions approaches have not been able to provide a sustainable resolution, due to advocacy efforts tend to be a massive confrontation, while mediation was only a procedural matter not a substantive matter.